Gender, Sufism, and Qur’anic Exegesis: Perceptions of Women’s Leadership within Sufi Orders in South Sulawesi - Damis, Rahmi; Nurbaethy, Andi; Arsyad, Aisyah; Matsyah, Ajidar; Lahmuddin, Fakhruddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study focuses on two key areas: the interpretation of Qur’anic verses regarding women’s leadership and its implementation within Sufi orders (tariqa) in South Sulawesi. The central question explored is how Sufi orders interpret these verses through a gender lens. To answer this question, a qualitative methodology employing interpretive and gender studies approaches was used. Data were collected through interview and literature review. The results of the research show that the perceptions of tarekat followers in South Sulawesi regarding the interpretation of verses regarding women's leadership in the public sphere. Some interpretations, based on Surah At-Tawbah [9:71], allow for women’s leadership by defining “awliya” as leaders, allies, and advisors, suggesting that both men and women can assume leadership roles if they possess the necessary competencies. Conversely, others, citing Surah An-Nisa’ [4:34], restrict women’s leadership. However, a closer examination indicates that Surah At-Tawbah [9:71] is a more general verse, while Surah An-Nisa’ [4:34] is context-specific, referring primarily to domestic matters. The implementation of leadership within Sufi orders is generally not at odds with these interpretations. In the public sphere, women have equal rights to men, including the right to vote and be elected. Moreover, there is no gender distinction in the concept of becoming a waliyullah, as exemplified by Rabi’ah al-Adawiyah. However, women have not yet assumed the role of murshid (spiritual guide) within Sufi orders due to several factors, including the historical precedent of male prophets and the physical and spiritual demands of the role. However, from a gender perspective, women often hold the position of khalifah (spiritual deputy) assisting the murshid in teaching and even coordinating regional activities.